Analysis of recombination and mutation events for 12 X-Chr STR loci: A collaborative family study of the Italian Speaking Working Group Ge.F.I. Issue 1 (December 2019) - Bini, C.; Di Nunzio, C.; Aneli, S.; Sarno, S.; Alù, M.; Carnevali, E.; Colao, E.; Di Nunzio, M.; Fabbri, M.; Fattorini, P.; Grignani, P.; Piccinini, A.; et al.
Abstract: According to the ISFG guidelines on the use of X-chromosome, the biostatistical evaluation in kinship analysis is based on a likelihood ratio approach, but since in calculation linkage and recombination events should be accounted for, an accurate estimate of mutation and recombination rates of X-markers analyzed is required. Due to the mode of genetic transmission and physical location, sometimes X-chromosome markers can be more informative than autosomal STRs and their analysis could be considered a supplementary tool in DNA testing. The increased demand to forensic laboratories for kinship investigations in complex cases explains the need not only to enlarge the Italian population database for 12 X-STRs routinely used for forensic application, but also to investigate the recombination fractions among markers. A collaborative exercise of the Italian Speaking Working Group Ge.F.I. was organized to evaluate mutation and recombination events in 12 X-STRs included in the Investigator Argus X12 kit. In order to explore the segregation stability, three-generation families (grandpa-mother-son) and two-generation families (mother-sons, father-daughters) for a total of 269 pedigrees were analyzed and calculations to estimate the recombination fractions between pairs of markers and mutation rates were performed. The statistical analysis showed evidence of inter- and intra-cluster recombination events, with almost free recombination for junction markers of linkage groups I and II and reduced recombination for linkage groups III and VI. We observed one- and two-step mutations, with an average value of 2.9 × 10 −3 .